Vendor Managed Inventory (VMI): From Theory to Practice. A Literature Review - Roba W.M. Salem; Adel Elomri (International Journal of Supply Chain Management, 2017)
This review paper considers a supply chain collaborative initiative which is Vendor Managed Inventory or VMI. VMI systems have received significant attention in the last two decades from researches worldwide due to its proved capability in effectively coordinating various parties in the supply chain through information sharing and exchange .In simple terms VMI allows suppliers to manage their retailers inventories and to decide on replenishment policies for their retailers. Generally contributions to literature of VMI are divided in to (1) Modeling of VMI systems (2)Practical implementation of VMI .This paper aims to analyze the various research aspects of VMI based on extensive literature search and to generate a classification scheme from which students, researches and practitioners can benefit. We could identify that there exists three different angles of research on VMI: (1) General (2) Modeling (3) Case studies. We further breakdown the classification to obtain the following classification scheme (1) Modeling (Mathematical/Simulation) (2) Case studies (3) Benefits (4) Challenges success factors. Under Mathematical model we have three subsections (1) Optimal replenishment dispatching policies (2) Pricing under VMI (3) VMI and contractual agreements.